STRENGTHENING VALUES IN LITHUANIAN JUDGES' ACTIVITY: DISCUSSION ON THE IMPLEMENTATION OF THE PRINCIPLE OF JUSTICE AND IMPARTIALITY - Navickienė, Žaneta; Žilys, Vaidotas (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
In today‘s guaranteeing of justice, the public becomes an active evaluator of the activities of courts and judges. The latest changes in the legal regulation since 2013 have enabled any member of the public to turn to the Judicial Ethics and Discipline Commission due to doubtful judge‘s behaviour. In addition, this commission was given a new function of giving consultations to judges. This shows that the increasingly attention of the scientists and practitioners is paid to the observance of the principles of professional ethics of judges, while the judges must consciously understand the meaning of ethical provisions in their professional activities and lives, constantly uphold the fundamental values.The aim of the paper is to analyse the principle of the ethics of Lithuanian judges – justice and impartiality. The analysis of the realization of this ethical principle in practice was carried out (49 decisions were analysed, among which 4 decisions adopted by the Judicial Ethics and Discipline Commission were relevant in this regard) which showed a high level of integrity of this principle. The research reveals two main vectors for the implementation of this principle of ethics by Lithuanian judges. Firstly, in the scientific and practical implementation of the principles of professional ethics there is a debate about its realization in practice (application). Secondly, this principle of the judge's ethics is most clearly elaborated by comparing the content of the principle of impartiality of the investigator or prosecutor.